Impact of human activities and livestock on the African environment: An attempt to partition the pressure - Leeuw, P.N. de; Reid, Robin S. (Food and Agriculture Organization of the United Nations, 1995)
The impact of human endeavours on the environment in the struggle to eke out a living through crop and animal agriculture is examined in a holistic context. Analyses focus on all the sources of pressure that modify the vegetation cover of rural Africa, including the effects of fires and burning of biomass, fuel wood extraction and deforestation and land clearing.